Detection of Human Brucellosis by Brucellacapt and Rose Bengal Test in the Endemic Area - Aydın, Elif; Dicle, Yalçın; Kaçtaş, Şerif; Gümüş, Ali Furkan (Fazile Nur Ekinci Akdemir, 2023)
[Abstract Not Available]
Keywords: Mikrobiyoloji; Klinik Tıp Bilimleri